STRUCTURAL MODELLING OF THE OIL POTENTIAL OF THE WEST CONGOLIAN SUB-BASIN THROUGH THE IDENTIFICATION OF GEOLOGICAL STRUCTURES AND GRAVIMETRIC ANOMALIES - Osée Mayinga Mayinga; Joël Etshekodi Lohadje; Franck Tondozi Keto; Prosper Aida Monkenya; Marlin Agolo Monza (Romanian Journal of Petroleum & Gas Technology)
The Democratic Republic of Congo has significant hydrocarbon reserves in its subsoil. The western Congo sub-basin is less explored in terms of oil potential. This study contributes to enriching the subsoil geological data by highlighting geological structures of major interest for oil exploration. This sedimentary basin is located in the Congo-Central province of the Democratic Republic of Congo and represents the main hope for oil prospects. With regard to the potential of this basin, it is worth mentioning that the presence of source rocks, oil showings, the presence of anticlines and faults identified in this study constitute potential traps for hydrocarbons. To date, the Western Congo sub-basin has been relatively unexplored. The satellite data have been compared with the tectonic field model in order to highlight the structural patterns of this vast basin. This research is crucial for informing future exploration initiatives and unlocking the hydrocarbon potential of the region, thus contributing to the country’s economic development.